The legal framework for refugee resettlement to the European Union with lessons from the American model - Prantl, Janine (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
This book elucidates the international and EU legal framework for refugee resettlement to the European Union. It identifies the international legal obligations of states applicable to resettlement and sets out the relevant EU legal bases of competence and limits to the exercise of competence. Finally, the legal dogmatic analysis, as well as a comparison with resettlement practices in the United States, serve as foundation for recommendations for a future EU legal framework.